Evaluation of the Attendance System Using the System Usability Scale Method at the Community Village Empowerment Office of Magetan Regency - Yyunan Inan Octafi'istoh; Ridho Pamungkas; Jini Ajeng Novitasari (Proceeding of the International Conference on Electrical Engineering and Informatics, 2024)
Advances in information technology have encouraged government agencies to implement electronic-based systems to improve the effectiveness, efficiency, and transparency of services. The Community and Village Empowerment Service of Magetan Regency uses the Presence and Performance Application System Si Apik application to record the attendance of State Civil Apparatus as part of the E-Government program. This study aims to evaluate the usability of the Si Apik application using the System Usability Scale method to measure the level of user satisfaction. The research approach involves descriptive qualitative and quantitative methods, with data collection through observation, SUS questionnaires, and semi-structured interviews. The results showed an average SUS score of 52.59, which is in the marginal category, with a grade D and an "OK" rating. This score indicates that the system still has technical constraints, such as network connections and application errors, which affect ease of use. Recommendations for improvement include optimizing features, increasing system stability, and providing clearer technical guidance. This study provides strategic input for the Community and Village Empowerment Service of Magetan Regency in improving the quality of Si Apik application services.